Insulin resistance and accelerated cognitive aging. (January 2023) - Abbasi, Fahim; Robakis, Thalia K.; Myoraku, Alison; Watson, Kathleen T.; Wroolie, Tonita; Rasgon, Natalie L.
Abstract: Insulin resistance may be an early sign of metabolic dysfunction with the potential to lead to neuropsychiatric sequelae in the long term. In order to identify whether insulin resistance in otherwise healthy young and middle-aged adults is associated with preclinical signs of neuropsychiatric impairment, we recruited 126 overweight but nondiabetic, nondepressed individuals who completed an insulin suppression test for direct measurement of insulin resistance as well as a battery of cognitive and neuropsychiatric measures. Insulin resistance was associated with weaker performance on a fine motor task (Purdue Pegboard) as well as increases in subclinical symptoms of depression. We submit that insulin resistance in early to mid-adulthood may be an important predictor of long-term risk for metabolic, psychiatric, and neurobehavioral dysfunction. Highlights: Insulin resistance may be an early sign of metabolic dysfunction with the potential to lead to neuropsychiatric sequelae in the long term. This paper describes associations of subclinical insulin resistance in healthy young and middle-aged adults with cognitive functioning and subclinical depressive symptoms. Insulin resistance was associated with impairment on a visuospatial task and increases in subclinical depressive symptoms. Insulin resistance was also associated with other markers of metabolic dysregulation, including hyperlipidemia and increases in fasting serum leptin, cortisol, and C-peptide. Insulin resistance in early to mid-adulthood may be an important predictor of long-term risk for metabolic, psychiatric, and neurocognitive dysfunction